2019
DOI: 10.1111/jcpe.13086
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of intrabony periodontal defects using rhFGF‐2 in combination with deproteinized bovine bone mineral or rhFGF‐2 alone: A 6‐month randomized controlled trial

Abstract: AimTo evaluate the use of recombinant human fibroblast growth factor (rhFGF)‐2 in combination with deproteinized bovine bone mineral (DBBM) compared with rhFGF‐2 alone, in the treatment of intrabony periodontal defects.Materials and MethodsPatients with periodontitis who had received initial periodontal therapy and had intrabony defects of ≥ 3 mm in depth were enrolled. Sites were randomly assigned to receive a commercial formulation of 0.3% rhFGF‐2 + DBBM (test) or rhFGF‐2 alone (control). Clinical parameters… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
69
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(78 citation statements)
references
References 44 publications
3
69
0
Order By: Relevance
“…Since 2016, rhFGF-2 has been used as a novel periodontal regenerative therapy in Japan (Saito et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Since 2016, rhFGF-2 has been used as a novel periodontal regenerative therapy in Japan (Saito et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In an earlier randomized control trial, our research group reported that combination therapy with rhFGF-2 and DBBM enhanced RBF compared with rhFGF-2 alone at 6 months postoperatively 20) . However, information is limited concerning longitudinal clinical outcomes with such therapy.…”
Section: Discussionmentioning
confidence: 98%
“…Use of 0.3% recombinant human fibroblast growth factor (rhFGF)-2 for periodontal regeneration received formal approval in Japan in 2016 20) . Recombinant human fibroblast growth factor-2 stimulates proliferation, differentiation, and angiogenesis in a variety of cells, and has been reported to be effective in regenerating periodontal tissue in animal models 14,27) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, our proposed strategy is to promote the concentration of FGF2 and other proangiogenic factors in the CM, while the application of the CM is controllable. Recombinant human fibroblast growth factor (rhFGF)-2 has been used clinically in periodontal regeneration therapy [45], whereas FGF-2modified MSC-derived CM provides some advantage over exogenous supplement of FGF-2 into the CM in that FGF-2-modified GMSCs not only produce and release more FGF-2, but also more VEGF-A, and TGF-β vs primary GMSCs. Briefly, an optimized conditioned medium by overexpressing the FGF-2 gene potentiates the angiogenic ability of hGMSCs.…”
Section: Discussionmentioning
confidence: 99%